Detection of Alive Human in Earth Quake Areas Using Arduino Controller - Sumathi R., Nandhini S., Kurinji Priya G., Nishaa S., Joshima A. (International Journal of Modern Agriculture, 2021)
In this project, a replacement approach for detective work alive humans in destructed environments employing a mobile automaton is projected. After natural disasters like earthquake and wave several humans can get at bay beneath fallen buildings, trees and broken vehicles a number of them are aware enough to shout dead set the rescue team to save lots of them however some are in unconscious state having no energy to decision dead set the rescue team. So, those individuals are left at bay while not being saved and even die. This paper presents the Alive Human detection. The event of automaton is split into 3 components that is that the hardware, electronic, and programming. The automaton has 4 DC motors for driving system and castor wheel for giving direction. Various sensors also are interfaced with Arduino Uno Board. Thermal camera to check for alive humans and for the programming half, Arduino IDE language was accustomed pass into to the developed application software system and shows the gap of survivors.